P586 Vedolizumab in Mild to Moderate Crohn's Disease Patients Naïve to Biological Therapy: a Multicentric Observational Study. (30th January 2023) - Dotti, A Z; Vilela, E G; Chebli, J M F; Chebli, L A; Magro, D O; Steinwurz, F; Argollo, M; Carvalho, N S; Parente, J M L; Parra, R S; Perin, R L; Flores, C; et al.
Abstract: Background: Vedolizumab, a human monoclonal antibody that blocks integrin α4-β7, was approved for the management of Inflammatory Bowel Diseases. In real-world experience the number of patients using vedolizumab as first-line biological therapy was low, mainly in Crohn′s Disease (CD). This study aimed to evaluate the efficacy of vedolizumab exclusively in CD patients who were naïve to previous biologics, with mild to moderate disease. Additionally, we aimed to analyze the safety profile of vedolizumab, rates of mucosal healing, need for abdominal surgery and drug discontinuation over time in this specific population. Methods: We performed a retrospective multicentric cohort study with patients with mild to moderate CD treated with VDZ who were naïve to previous biologics agents. These patients had clinical activity scores (Harvey-Bradshaw Index [HBI]) measured at baseline and weeks 12, 26, 52 as well as at the last follow-up. Clinical response was defined as a reduction ≥3 in HBI whereas clinical remission as HBI ≤4. Mucosal healing was defined as the complete absence of ulcers in control colonoscopies. Kaplan-Meier survival analysis was used to assess the persistence with vedolizumab over time. Results: From a total of 72 patients (6 excluded) 53% (35/66) reached clinical remission at week 12. This percentage increased to 71.9% (46/64) at week 26, 88.1% (52/59) at week 52 and 81.8% (54/66) at the last follow-up visit. Clinical response was achieved in 72.7% (48/66), 92.2% (59/64), 95, 1% (58/61) and 83.3% (55/66) in the same periods, respectively. Mucosal healing was achieved in 62.3% (33/57) of patients. Vedolizumab was well-tolerated and most adverse events were minor; 89.3% remained on vedolizumab after 52 weeks. During vedolizumab treatment, 3/66 patients underwent surgery. Conclusion: Vedolizumab was effective in the management of patients with mild to moderate CD as first biological agent, with a remission rate of 88.1% after one year. Mucosal healing was observed in 62.3% of patients and major abdominal surgery was needed in only 4.5% of patients. This is one of the first international studies focused on the use of vedolizumab as a first-line biological treatment option in clinical practice in mild to moderate CD.